Indigenous African enterprise : the Igbo traditional business school (I-TBS) - Adeola, Ogechi (Bingley : Emerald Publishing Limited, 2020)
This volume of Advanced Series in Management traces the origins, development, and key themes of the business practices of Nigeria's south-eastern Igbos including apprenticeships, entrepreneurial clusters, sales practices, conflict management, talent recruitment, indigenous financial practices, locally-generated venture capital, family businesses, and succession planning. The Igbo Traditional Business School (I-TBS) is not a conventional academic institution as it operates outside the classroom. Though without a library, or even an address, its tradition of lifelong entrepreneurial learning is an important area to explore. At a time when there is increased interest in Africa-centric business models, it is valuable to consider sustainable business prototypes built on established cultural practices, norms, and values. Academics will find the examination of innovative I-TBS business practices, a valuable contribution to sustainable development discourse in Africa and frontier markets. Practitioners and policymakers will gain insights into the unique practices of an indigenous entrepreneurship system in an African context, with implications for socioeconomic advancements.
Foreword by Azubuike Sonny Nwankwo Part A. An introduction to the Igbo Traditional Business School (I-TBS) Chapter 1. The Igbo Traditional Business School (I-TBS): An Introduction; Ogechi Adeola Chapter 2. Igba-Boi: Historical Transitions of the Igbo Apprenticeship Model; Adebukola E. Oyewunmi, Olabode A. Oyewunmi, and Chinonye L. Moses Chapter 3. Entrepreneurship Incubation Among the Nigerian Igbos: The Íǥba-Bọị Indigenous Model; Anayo D. Nkamnebe and Esther N. Ezemba Chapter 4. The Igbo Traditional Business School (I-TBS): A SWOT Review Synthesis; Ishmael Obaeko Iwara Part B. Indigenous Business Management and Succession Planning Chapter 5. Family Business, Succession Planning and Survival Strategies; Okey Nwuke, Chiz Nwoye, and Nnaemeka J. Onoyima Chapter 6. Talent Management and Succession Planning in Traditional Igbo Businesses; Chidi Okoro and Nkemdilim Iheanachor Chapter 7. Talent Recruitment, Knowledge Management and Business Performance: A Case Analysis of Igbo Traders in Lagos State; Ngozi Ann Chikere, Adenike Aderonke Moradeyo, and Isaiah Adisa Part C. Financial Practices, Sales Negotiation and Conflict Management Chapter 8. Cultural Practices in Sales Negotiations: Insights from the Indigenous Igbo Trade Practice; Uche Attoh, and Ademola Ajeyomi Chapter 9. Understanding the Conflict Management and Transformation Mechanisms in the Igbo Traditional Business Model; Silk Ugwu Ogbu Chapter 10. Indigenous Financial Practices of Igbo Micro-Entrepreneurs in Lagos; Ogechi Adeola, Uchenna Uzo, and Adedeji Adewusi Part D. Business Incubators and Models Chapter 11. Indigenous Business Incubators: A focus on the Akwete Weaving Industry; Victoria Okafor, Ogechi Adeola, and Afam Ituma Chapter 12. Mutual Aid Economy: Exploring the Locally-Generated Venture Capital Approach In Igbo Business Industrial Clusters; Awele Achi and Francis Achi Chapter 13. Nollywood: Exploring the History and Indigenous Distribution Structure of the Igbos; Ngozi Okpara Chapter 14. Profiling the Socio-Cultural Attributes of Igbo Business Incubation in Diaspora: The South African Experience; Kingsley Ekene Amaechi Part E. Recommendations for Policy and Practice Chapter 15. Igba-Boi: Comparison with the German Model and Recommendations for the Nigerian Economy; Obinna Ikwuegbu, Oluyemisi Bolade-Ogunfodun, Kola Yusuff, and Bernd Vogel Chapter 16. The Igbo Business Practice: Towards a Model for Africa -- Conclusion and Recommendations; Ogechi Adeola.
eBooks on EBSCOhost
Keywords: Igbo (African people) -- Economic conditions; Business enterprises -- Nigeria; Entrepreneurship -- Nigeria; Ibo (Peuple d'Afrique) -- Conditions économiques.; Entreprises -- Nigeria; Entrepreneuriat -- Nigeria; Nigeria; History, Africa, West; Business enterprises; Entrepreneurship; Igbo (African people) -- Economic conditions; Nigeria